2018
DOI: 10.3832/ifor2502-011
|View full text |Cite
|
Sign up to set email alerts
|

Stand structure and regeneration of Cedrus libani (A. Rich) in Tannourine Cedar Forest Reserve (Lebanon) affected by cedar web-spinning sawfly (Cephalcia tannourinensis, Hymenoptera: Pamphiliidae).

Abstract: The analysis of forest structure is a useful tool to understand stand biodiversity characterizing forest ecosystems, and could help in suggesting appropriate management plans. Cedar forests in Lebanon are remnant patches that survived past human activities but are still threatened by other different anthropogenic and natural disturbances. Among these threats, the cedar web-spinning sawfly (Cephalcia tannourinensis) discovered in Tannourine Cedar Forest Nature Reserve in 1997, which is able to cause the death o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In the PRCSA and PRCSB the basal area of the species is 36.47 and 38.49 m 2 •ha -1 respectively (Table 1). These values are higher compared to the value of C. libani basal area referred for stands in Tannourine Cedar Forest Reserve in Lebanon (Bassil et al 2018), but they are lower than the basal area of pure C. atlantica forests in Theniet El Had National Park in Algeria (Sarmoum et al 2018) and the values of C. atlantica basal area of most closed stands in the Moroccan Middle Atlas forests (Linares et al 2011). In Cyprus, two groups of pure structural types are formed regarding basal area.…”
Section: Discussionmentioning
confidence: 80%
“…In the PRCSA and PRCSB the basal area of the species is 36.47 and 38.49 m 2 •ha -1 respectively (Table 1). These values are higher compared to the value of C. libani basal area referred for stands in Tannourine Cedar Forest Reserve in Lebanon (Bassil et al 2018), but they are lower than the basal area of pure C. atlantica forests in Theniet El Had National Park in Algeria (Sarmoum et al 2018) and the values of C. atlantica basal area of most closed stands in the Moroccan Middle Atlas forests (Linares et al 2011). In Cyprus, two groups of pure structural types are formed regarding basal area.…”
Section: Discussionmentioning
confidence: 80%
“…Investigation and analysis of stand structure can help us understand the history, current situation, and future development of forest ecosystems and thus carry out appropriate management practices [ 26 , 30 ]. The structural characteristics of the stand affect the spatial and temporal distribution of regeneration, the quantity and quality of provenance, and the growth and death of individuals [ 4 , 6 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…koraiensis seedlings in all experiment sites increased with the increase of opening degree in the same aspect [ 29 ]; medium mingling and random distribution were suitable for artificial regeneration of Pinus koraiensis seedlings in the secondary forest [ 28 ]. Spatial pattern analysis showed that there was a positive spatial relationship between mature Lebanese cedar trees as well as between mature and juvenile cedars [ 30 ]. Through quantifying the competitive influence of neighboring trees, Saha et al [ 31 ] indicated that the height to DBH ratio of young oak ( Quercus robur ) significantly increased with aggregate and intraspecific competition, but interspecific competition had no significant effect on the height to DBH ratio.…”
Section: Introductionmentioning
confidence: 99%
“…dead vs living). For all analysis types, positive, negative, or absence of departure from the null model simulation envelopes occurs at a given scale r Hao et al 2007;De Luis et al 2008;Navarro-Cerrillo et al 2013;Kang et al 2014;Cordero et al 2016;Hu et al 2017;Miao et al 2018;Bassil et al 2018;Zhang et al 2020;Wang et al 2020b Paircorrelation function g(r) (Stoyan and Stoyan 1994) g(r) = 1 Points of the pattern are randomly distributed g(r) > 1 Points of the pattern are aggregated g(r) < 1 Points of the pattern are segregated Pélissier 1998;Wiegand et al 2007a;Suzuki et al 2008;LeMay et al 2009;Comas et al 2009;Batllori et al 2010;Wang et al 2010a;Zhang et al 2010;Martínez et al 2010;Lan et al 2012;Liu et al 2014;Petritan et al 2014;Velázquez et al 2014;Petritan et al 2015;Wang et al 2015 ;Jácome-Flores et al 2016;Nguyen et al 2016;Janík et al 2016;Fibich et al 2016;Gradel et al 2017;Wang et al 2017;Erfanifard and Stereńczak 2017;Collet et al 2017;Ghalandarayeshi et al 201...…”
Section: Second-order Summary Statisticsmentioning
confidence: 99%
“…dead vs living). For all analysis types, positive, negative, or absence of departure from the null model simulation envelopes occurs at a given scale r (Continued) Iszkuło et al 2012;Zhang et al 2013;Navarro-Cerrillo et al 2013;Ebert et al 2015;Wehenkel et al 2015;Jácome-Flores et al 2016;Jia et al 2016;Zhang et al 2016;Owen et al 2017;Gradel et al 2017;Zheng et al 2017;Nguyen et al 2018b;Omelko et al 2018;Muvengwi et al 2018;Vandekerkhove et al 2018;Kazempour Larsary et al 2018;Lv et al 2019;Baran et al 2020 Patterns 1 and 2 are segregated Riginos et al 2005;Hao et al 2007;De Luis et al 2008;Batllori et al 2010;Navarro-Cerrillo et al 2013, Kang et al 2014Cordero et al 2016;Hu et al 2017;Miao et al 2018;Bassil et al 2018; Wang et al 2010a;Zhang et al 2010;Martínez et al 2010;Lan et al 2012;Liu et al 2014;Petritan et al 2014Petritan et al , 2015Wang et al 2015;…”
Section: Second-order Summary Statisticsmentioning
confidence: 99%